DYSFUNCTIONAL SEMANTIC ROLE OF LANGUAGE IN LITERARY TEXTS: A CASE STUDY ON HAROLD PINTER’S MOUNTAIN LANGUAGE - Yadgar Faeq Saeed; Areen Ahmed Muhammed (Universitas Islam Sumatera Utara (UISU), 2019)
Language and literature are two inseparable subjects, one of which cannot be fully functional with the absence of the second part. This article shows the dysfunction of semantics in Harold Pinter’s Mountain Language. For many years, scholars and linguists work separately on different cases regarding literary texts or linguistics obstacles. From this paper, a new path will be saved for future references and works to bring both cases together and show their roles on one another. Moreover, literary works pay less attention to grammatical rules and plenty of dysfunctional languages can be examined and seen. In addition, several external factors can be the obstacle of using functional and accurate language use semantically and systematically. Moreover, political or social violence have become major points in many literary topics in the modern era. This study deals with theoretical aspects of society starting from family up to community and government. Additionally, the absence of semantics in the language of this drama is not neglected arbitrarily; whilst, there is a loop of violence. There are some basic theories related to the topic that this paper will examine. It includes the theory of Grice’s maxims (Gricean maxims) and the role of semantics when it comes to politics and power. Finally, the paper alienates all the curtains and shows the role of power, gender differences, class status, and diversity on language use in many areas.